2017
DOI: 10.1158/1541-7786.mcr-17-0135
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Molecular Profiling of Olfactory Neuroblastoma Identifies Potentially Targetable FGFR3 Amplifications

Abstract: Olfactory neuroblastomas (ONBs), also known as esthesioneuroblastomas, are malignant round-cell tumors that represent up to 5% of sinonasal malignancies. Despite their aggressive course, molecular studies of ONBs have been limited, and targeted therapies are lacking. To identify potential oncogenic drivers and targetable pathways in ONBs, we characterized 20 ONBs, including archived ONBs profiled by targeted, multiplexed PCR (mxPCR)-based DNA next-generation sequencing (NGS) of the coding sequence of over 400 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…These results indicate a limited therapeutic benefit of EGFR inhibitors in ONB patients. Mutations in TP53 gene were also detected in other studies that performed DNA sequence analysis in ONB samples [ 13 17 ]. Due to the disease progression in those patients, a role of TP53 mutation as an unfavorable prognostic and predictive factor in ONB has been suggested [ 18 ].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…These results indicate a limited therapeutic benefit of EGFR inhibitors in ONB patients. Mutations in TP53 gene were also detected in other studies that performed DNA sequence analysis in ONB samples [ 13 17 ]. Due to the disease progression in those patients, a role of TP53 mutation as an unfavorable prognostic and predictive factor in ONB has been suggested [ 18 ].…”
Section: Discussionmentioning
confidence: 54%
“…Currently only a few studies have investigated genomic landscape of ONBs, using different sequencing techniques [ 13 17 ]. Furthermore, in three of these studies the potential of targeted therapy with specific drugs was explored.…”
Section: Introductionmentioning
confidence: 99%
“…reported different mutational profiles in low‐grade and high‐grade ONBs, with no recurrent mutations in low‐grade ONBs, and IDH2 and TP53 mutations in higher‐grade ONBs. TP53 mutations have also been reported by others in high grade ONBs . It is possible that high‐grade tumours have a higher mutational load than low‐grade tumours, or have mutations that are more immunogenic.…”
Section: Discussionmentioning
confidence: 55%
“…This might be due to the stronger immunogenic profile of high‐grade tumours. The mutational landscape of ONBs is still poorly known . Classe et al .…”
Section: Discussionmentioning
confidence: 99%
“…This is evidenced by recent case reports showing durable responses in patients treated with tyrosine kinase inhibitors after identifying particular mutations, such as, EGFR (cetuximab), RET (sunitinib), PDGFRB (sunitinib), and KIT (imatinib), and also in a patient treated with anti‐vascular endothelial derived growth factor (VEGF) therapy (bevacizumab) . What is more, recent studies have revealed targetable genomic lesions in canonical signaling pathways in primary ENB samples, including FGFR , PIK3CA , PTEN , and NF1 , several members of the Wnt/β‐catenin pathway, as well as mutations in critical regulators of the cell cycle, such as CDKN2C and CDKN2A . All of these somatic alterations could offer therapeutic opportunities in ENB.…”
Section: Discussionmentioning
confidence: 94%